An analysis of seasonality of sarcoidosis in the United States veteran population: 2000-2007 - Gerke, A.K.; Tang, F.; Yang, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: The onset of sarcoidosis is thought to be seasonal, particularly Lofgren’s syndrome. However, there are conflicting data on seasonality by country and by radiographic stage. Objective: The objective of this study was to determine if there is seasonality of the diagnosis of sarcoidosis in outpatients in the United States. Methods and Results: Using time series methods, we performed a retrospective analysis of 3791 incident cases of sarcoidosis in the Veteran’s Health Administration national outpatient claims database (2000-2007). We did not find overall seasonality in the occurrence of new sarcoidosis in United States Veterans (p=0.9860), even after we subdivided the United States by northern (p=0.6824) and southern regions (p=0.4588). Conclusion: The lack of seasonality in this study indicates that season is not a dominant factor in complex gene-environment-host interaction that precedes presentation of new sarcoidosis cases in the United States Veteran population.